Association of Pre-Operative Risk Factors with Abdominal Wound Dehiscence - Durrani, Kamran khan; Ilyas, Sohail; Shah, Usman; ., Naveed; Rehman, Ateeq Ur; Rehman, Habib Ur (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the association of pre-operative risk factors with abdominal wound dehiscence.Study Design: Quasi-experimental study.Place and Duration of study: Surgical Unit 1 of Combined Military Hospital, Rawalpindi, Pakistan from, Aug 2019 - Jan 2020.Methodology: A total of 130 cases and 130 controls with ages 20 to 70 yrs were included. Patients with neurological or psychological disorders or who underwent a laparoscopic procedure were excluded. All surgeries were performed by a single team with the assistance of a researcher. Patients were divided into two groups, i.e., Cases with abdominal wound dehiscence and controls without abdominal wound dehiscence. Patients were evaluated for risk factors, i.e., advanced age, male gender, anemia, emergency surgery, diabetes, and hypertension.Results: Mean age of patients in case group was 46.69±10.16 years, and in control group was 44.57±10.35 years. Preoperative risk factors for abdominal wound dehiscence in cases and controls were as follows; advanced age (7.69% vs. 3.08%), male gender (37.69% vs. 32.31%), hypertension (40% vs. 21.54%), diabetes (30.77% vs. 20.0%), anemia (83.08% vs. 50.0%) and emergency surgery (70.77% v. 48.46%).Conclusion: Risk factors like hypertension, diabetes mellitus, anemia and emergency surgery are the major risk factors for abdominal wound dehiscence.